Cost-effectiveness analysis of a quality improvement program to reduce caesarean sections in Brazilian private hospitals: a case study - Rosa Maria Soares Madeira Domingues; Paula Mendes Luz; Barbara Vasques da Silva Ayres; Jacqueline Alves Torres; Maria do Carmo Leal (BMC, 2021)
Plain English summary Caesarean section is a safe intervention to save the lives of women and newborns. However, it is associated with negative health consequences for women and children in the short, medium and long term. Therefore, its harmful effects can outweigh its benefits when used excessively. Caesarean rates are increasing globally. In Brazil, caesarean section is the most frequent type of birth since 2009. In 2015, a quality improvement project, called "Adequate Childbirth Project" (PPA), was implemented in Brazilian public and private hospitals with the aim of improving the quality of childbirth care and reducing caesarean sections without clinical indications. In this study, we compared the caesarean rate and the hospitalization costs of women assisted in this new model of care and in the standard of care model. The women attended in the PPA model of care had a lower rate of caesarean section (31.7% vs 88.6% in the standard of care model), with no differences in severe negative maternal and neonatal outcomes. Women in the PPA model of care also had a higher frequency of spontaneous or induced labor and a lower frequency of early term births, that is, less than 39 weeks of gestation. The PPA model of care was considered cost-effective, that is, it produced good results for the amount of money spent. This is a promising result for services that face the problem of increasing numbers of caesarean sections and are looking for strategies to improve the quality of childbirth care.